Here and now: Lived experiences of professional nurses practising caring presence in a rural public hospital in the North West Province, South Africa - Petronella S. Hobbs; Emmerentia du Plessis; Petronella Benadé (AOSIS, 2020)
Background: Practising caring presence is recognised as an important nursing intervention indispensable to high-quality, patient-centred care. An awareness of the real world of professional nurses (PNs) practising caring presence will assist in expanding and supporting the existing literature on the same. A clear and rich description of what the concept of caring presence entails within the unique South African nursing context may guide nurses in the art of this nursing skill, enhance their professionalism and facilitate the formulation of recommendations on how to encourage nurses to implement the practice of caring presence within nursing. Aim: This study explored and described the lived experiences of PNs practising caring presence in a rural public hospital. Setting: The study setting was a 120-bed, level-two district hospital in the North West Province of South Africa. Methods: A descriptive phenomenological method, specifically Husserl's approach, informed this study. Semi-structured interviews were conducted with a purposive sample of 10 PNs. Data were coded and analysed using Colaizzi's seven-step method. Results: Five themes emerged from the data analysis: professional caring presence, ethical caring presence, personal caring presence, healing caring presence and what caring presence is not. Conclusion: Professional nurses experience practising caring presence as professionally and personally fulfilling, as an expression of their passion for the profession, as a way of portraying ethical care, as a willingness to be personally present and as a healing experience that involves commitment and taking care of patients holistically. Unprofessional, unethical behaviour and depersonalisation of patients were indicated as uncaring behaviour.